Benchmarking Solar Pump Performance: Off-Grid Solar Irrigation Pumps in Eastern and Central India - Verma, Shilp; Kuriachen, Philip; Bhattacharjee, Suchiradipta; Sharma, Laxmi; Basu, Subhodeep; Usadadia, Nikunj (International Water Management Institute, 2025)
This brief describes a three-state field study initiated by the Solar Energy for Rural Livelihoods (SE4RL) project with the objective of understanding the drivers of performance for off-grid solar irrigation pumps. The study covered approximately 300 solar irrigation systems in Bahraich (Uttar Pradesh), Samastipur and Muzaffarpur (north Bihar), and East Singbhum (Jharkhand) to document usage patterns, irrigated area, revenue generation, equity of access, and operational efficiency. By analyzing these parameters, the study seeks to identify what drives high performance and where improvements are needed.